Analisis Pengaruh Pembiayaan Mikro Terhadap Peningkatan Pendapatan Pelaku Usaha UMKM di Bank Syariah Indonesia KCP Pandaan A Yani Pasuruan - Wirda Isti’anatuz Zulfa; Sukamto Sukamto; Aslikhah Aslikhah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of microfinance on increasing the income of MSMEs at Bank Syariah Indonesia (BSI) Pandaan A Yani Branch, Pasuruan. Islamic banking plays a crucial role as an intermediary institution that collects and distributes funds to the public, particularly in supporting the development of the Micro, Small, and Medium Enterprises (MSMEs) sector, which forms the backbone of the national economy. However, limited capital remains a major obstacle for MSMEs in developing their businesses. This study employed a quantitative approach using a survey method through the distribution of questionnaires to microfinance customers. The data obtained were then analyzed using simple linear regression to determine the relationship between microfinance and income growth. The analysis results indicate that microfinance has a positive and significant impact on increasing the income of MSMEs. This demonstrates that microfinance disbursed by Bank Syariah Indonesia can help entrepreneurs increase their business capacity and income. Therefore, microfinance serves not only as a source of funding but also as an instrument for improving the economic welfare of the community. This research is expected to contribute to the development of Islamic banking, particularly in optimizing microfinance for MSMEs.